The essence of liberty : free black women during the slave era - King, Wilma, 1942- (University of Missouri Press, 2006)
"King uses a wide range of sources to examine the experiences of free black women in both the North and the South, from the colonial period through emancipation, showing how they became free, educated themselves, found jobs, maintained self-esteem, and developed social consciousness--even participating in the abolitionist movement"--Provided by publisher.